The influence of the offer of organic products on consumer purchasing decisions - Pereira, Ana Margarida Simões Alves (My University, 2024)
The global organic products market has been showing increasing growth rates since the beginning of the century, affecting consumers' purchasing decisions. However, the existence of organic products also influences supermarkets, the brands that sell their products in these places and the country's economy itself. During the thesis, the aim is to understand how non-organic consumers' buying decisions are influenced by the marketing tactics, availability, familiarity, and social perceptions of organic products. Most of the studies carried out in this sense follow a quantitative approach with organic consumers, contrary to the present study, with a qualitative approach analyzing non-organic consumers. Data collection included semi-structured interviews, whose main results is that the behavior of non-consumption of organic products by consumers is affected not only by their availability and price, but also by the opinions of other consumers and by the marketing strategies developed by brands. The behavior studied included non-regular consumers and non-consumers of organic products. It is therefore recommended that brands consider this segment in their marketing strategies, to increase their outreach power in terms of consumers and enhance the size of the organic products market.
Keywords: Consumer behavior; Organic products; Motivations not to consume; Social perception